أساليب الملأ في مواجهة دعوة الأنبياء في القرآن الكريم: دراسة دلالية بيانية: Elites’ Methods in Confronting Prophets’ Call in the Holy Quran: A Semantic and Rhetorical Study - Ali Abdallah Ahmad Al-Hrerat (Maʿālim al-Qurʾān wa al-Sunnah, 2024)
The study aimed to explain the methods and role of elites in confronting Prophets’ calls in the Holy Quran, as well as the rhetorical connotations they contained. It also aimed to identify and address these methods, and to clarify the extent of their influence on the call. The researcher employed the inductive method to track these methods, and the deductive method to infer the meanings inherent in the word's use, the Quranic structure, the Prophets’ story, and the rhetorical features. The study elucidated the strategies employed by Elites in response to the call, illustrating them through the biographies and stories of prophets. This provided preachers with a framework to follow and emulate, guiding them in addressing the call’s consequences and responsibilities, and in promoting positive values within societies that steer clear of despair and hopelessness. The study concluded with a series of significant findings, the most significant of which was that the Holy Qur'an contains a variety of elite methods, including the use of vocabulary and structures. These methods demonstrate the extent of elite influence in achieving a surface aversion to the call and its failure to achieve its true goal, as well as the wisdom of the prophets in rejecting these methods in order to uphold the laws of the struggle between good and evil.